KONSEP EKONOMI POLITIK DALAM PERSPEKTIF IBNU KHALDUN - Muhammad Alif Al Insany; R. Moh. Qudsi Fauzi (Universitas Airlangga, 2019)
This research aimed to find out the political economy concepts existed in Ibn Khaldun’s thoughts through his magnum opus of Muqaddimah which was a part of Al-Ibar book. This research used literature study method by studying the literature related to poitical economy. Literature data interpretation has been done by historical analysis technique which consists of periodization stages based on the life of Ibn Khaldun, and by historical descriptive analysis technique which is related to the political economy thoughts of Ibn Khaldun. This research showed that economics and politics have a relation since in the past, especially in a life span of Ibn Khaldun and his thoughts about political economy, such as production, work division, wage theory, etc. These thoughts was firstly presented by Ibn Khaldun before classical period economists did. Therefore, these thoughts is very important to study further to provide suggestions for economic studies, especially islamic economic studies.Keywords: Political Economy, Ibn Khaldun, Economic PoliticsREFERENCES Abu-Hantash, Tawfiq F. 1983. Ibn Khaldun and the City: A Study of The Physical Formation of Medieval Cairo.Afrizal. 2014. Metode Penelitian Kualitatif Sebuah Upaya Mendukung Penggunaan Penelitian Kualitatif dalam Berbagai Disiplin Ilmu. Jakarta: Rajawali Press.Al-Hamdi, Mohaned Talib. 2016. Ibn Khaldun: The Father of the Division of Labor.Boulakia, Jean David C. 1971. Ibn Khaldun: A Fourteenth Century Economist. The Journal of Political Economy.Deliarnov. 2006. Ekonomi Politik.Jakarta: Penerbit Erlangga.Hamid, Edy Suandi. 2009. Akar Krisis Ekonomi Global dan Dampaknya Terhadap Indonesia. La Riba Jurnal Ekonomi Islam. Vol III.Hardoon, Deborah. 2017. An Economy For The 99%. Oxfam.Heridansyah, Rizki. 2011. Pengaruh Pengalaman Kerja dan Tingkat Upah Terhadap Produktivitas Pekerja di UD. Farley’s Kota Mojokerto. Unesa.Ibandi, Ahmad. Dkk. 2017. Politik Ekonomi Islam Analisis Wacana Keislaman Abad VII-XIX M. Yogyakarta: LESFI.Iqbal, Ichsan. 2012. Pemikiran Ekonomi Islam Tentang Uang, Harga dan Pasar. Jurnal Khatulistiwa – Journal of Islamic Studies, Volume 2.Khaldun, Ibn. tth. The Muqaddimah An Introduction to History. Terjemahan dari Bahasa Arab oleh Franz Rosenthal. 1967. London: Routledge & Kegan Paul Ltd._____. 2001. Mukaddimah Ibnu Khaldun. Terjemahan oleh Masturi Irham, Malik Supar, dan Abidun Zuhri. 2011. Jakarta: Pustaka Al-Kautsar.